Patterns of nutrient limitation on periphyton in a tropical black-water lake depend on the relative contribution of autotrophic and heterotrophic components. Issue 1 (2nd January 2019) - Sanches, Lúcia Fernandes; Guariento, Rafael Dettogni; Esteves, Francisco de Assis; Bozelli, Reinaldo Luiz; Caliman, Adriano
ABSTRACT: This study addressed the occurrence of resource co-limitation of periphytic communities in a tropical black-water lake. We performed a field experiment using nutrient diffusing substrates to create treatments with nitrogen (N) and phosphorus (P) amendments. Two light levels were considered: high light (near the water surface) and low light (near the lake bottom). Periphyton nutritional limitation was also assessed using available literature on optimal stoichiometric ratios. Based on the stoichiometric ratios, we found that the periphytic autotrophic community was mostly N-limited. However, we observed higher values of total biomass (carbon [C]: mg m −2 ) in treatments with N and P joint addition and lower values of carbon to chlorophyll a (C:Chl -a ) ratio in treatments with only N addition. We concluded that N limitation primarily affected the the algal periphytic community, and the N and P co-limitation primarily affected the total periphytic biomass, which also includes heterotrophic organisms. Our results of stoichiometry and periphyton development support the occurrence of N and P co-limitation at the community scale. Our results ultimately support the primacy of co-limitation as hierarchical levels of organization increase in biological systems, such as periphytic communities composed of diverse taxa.